2018
DOI: 10.5897/err2017.3392
|View full text |Cite
|
Sign up to set email alerts
|

Achievement goals of medical students and physicians

Abstract: In achievement settings, the types of motivation individuals develop are crucial to their success and to the ways in which they respond to challenges. Considering the competitive nature of medical education and the high stakes of medical practice, it is important to know what types of motivation (conceptualized here as achievement goals) medical students and physicians adopt and how these may differ depending on the nuances of their achievement settings. This is a cross-sectional survey study of medical studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This study is part of a larger research project investigating personal and contextual factors in the learning and wellbeing of medical students and practicing physicians. The findings on student and physician motivation and lifelong learning have been reported elsewhere [16,17,18,19]. In the present study, we examined the association of physicians’ self-compassion with work engagement, exhaustion, and professional life satisfaction.…”
Section: Methodsmentioning
confidence: 55%
“…This study is part of a larger research project investigating personal and contextual factors in the learning and wellbeing of medical students and practicing physicians. The findings on student and physician motivation and lifelong learning have been reported elsewhere [16,17,18,19]. In the present study, we examined the association of physicians’ self-compassion with work engagement, exhaustion, and professional life satisfaction.…”
Section: Methodsmentioning
confidence: 55%
“…It is important to acknowledge institutional and cultural specificities that could have influenced the present results, for example, the predominance of mastery avoidance-oriented students (83%). Most studies until now have pointed to a mastery approach predominance of medical students’ goals [ 62 ]. However, none of them, for the best of our knowledge, were performed in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of the study, it can be stated that most of the pre-service Turkish teachers have learning-approach achievement goal, that some of them have learning-avoidance achievement goal, and that fewer have performance-approach achievement goal. In this regard, it can be concluded that the academic performance of the participants is positively affected and increased when they acquire achievement, and this opinion is an indication that the pre-service teachers have a learning-approach achievement goal at this point (Akın and Arslan, 2014;Babenko, Daniels, White, Oswald andRoss, 2018 Kayis andCeyhan, 2015;Toğluk, 2009).…”
Section: Discussionmentioning
confidence: 99%